Relationship between maxillary sinus volume and nasal septal deviation concha bullosa and infundibulum size using cone-beam computed tomography (CBCT) - Azadeh Zakariaee Jubari; Azadeh Torkzadeh (Babol University of Medical Sciences, 2022)
Introduction: The maxillary sinuses are the largest paranasal sinuses adjacent to the teeth. Due to anatomical variations in different people, knowledge of these variations is essential for rhinoplasty and sinusitis. The aim of the present study was to determine the relationship between maxillary sinus volume with nasal septal deviation, concha bullosa and infundibulum size using cone-beam computed tomography (CBCT). Materials & Methods: In this descriptive -analytical study, CBCT images of 135 patients who underwent maxillofacial imaging were evaluated. In order to measure the volume of maxillary sinuses, CBCT images of axial sections were used with a thickness of 2 mm and Digimizer image analysis software. In the coronary section of nasal septum deviation, types of concha bullosa and infundibulum size were determined. Data were analyzed using one-way ANOVA, paired t-test, Pearson correlation test and regression. A value of P<0.05 was considered significant. Results: There was a significant inverse relationship between the mean of volume of the right sinus (p=0.012, r=-0.216) and left sinus (p<0.001, r=-0.303) with the deviation of the nasal septum. A significant inverse relationship was found between the mean volume of right maxillary sinus (p<0.012, r=-0.357) and left maxillary sinus (p=0.006, r=-0.357) with infundibulum size. The mean volume of right and left sinues from coronal view was not significantly different in the presence or absence of concha bullosa.  There was no significant difference between male and female in the mean volume of the right and left sinuses. Conclusion: The present findings suggest that maxillary sinus volume is smaller the deviation in moderate and severe septal deviation cases and that the maxillary and with increasing size of infandibulum, the volume of maxillary sinus was larger.